Convergence of Gene Therapy and Vaccine Platforms in the Post-Pandemic Era: A Mini Review - Huynh, Thu-Thao Thi; Nguyen, Thi Nga; Nguyen, Tuan Anh; Nguyen, Anh-Duy Hoang; Quang, Minh Trong (Trends in Sciences, 2025)
The COVID-19 pandemic accelerated the convergence of vaccine and gene therapy research, demonstrating the potential for gene-encoded platforms to be rapidly reconfigured for both preventive and therapeutic applications. This real-world evaluation validated the principle of adaptable, platform-based molecular medicines. Convergence is facilitated by three key components: Chemically modified nucleotides that reduce innate-immune sensing while maintaining high translation efficiency, lipid nanoparticles refined for targeted and low-toxicity delivery, and viral vectors with adjustable immunogenicity. Emerging technologies, including self-amplifying RNA, selectively targeted lipid nanoparticles, and advanced adenoviruses, have expanded the therapeutic toolkit to include in vivo genome editing and personalized neoantigen vaccines. The rapid scale-up of production during the pandemic has had a lasting impact, establishing cGMP manufacturing lines, emergency-use regulatory frameworks, and extensive safety data. However, the field still faces challenges such as context-dependent immunogenicity, the need for thermostable products to improve global distribution, and widening disparities in technology access between high- and low-income regions. Gene-encoded platforms have evolved from a proof-of-concept to a multifaceted therapeutic framework capable of addressing infectious, genetic, and malignant diseases. Their full public health potential will depend on coordinated investment in distributed manufacturing, adaptive regulation, and ethical governance that prioritizes equity alongside technical advancements. HIGHLIGHTS The COVID-19 pandemic served as a major catalyst, accelerating the convergence of gene therapy and vaccine development into a unified field of adaptable, gene-encoded molecular medicines. A bidirectional flow of innovation is detailed, where foundational gene therapy research (e.g., modified nucleotides, lipid nanoparticles) enabled rapid vaccine success, which in turn established manufacturing and regulatory precedents that now benefit therapeutic development. The validation of mRNA and adenoviral vector platforms is expanding the therapeutic toolkit, driving progress in protein replacement therapies, in vivo genome editing, and personalized cancer immunotherapy. Future progress depends on overcoming shared challenges, including managing context-dependent immunogenicity, ensuring thermostability for global distribution, and establishing equitable access through distributed manufacturing and adaptive governance. GRAPHICAL ABSTRACT